(untitled) (Editora Impacto Científico, 2024)
The study discusses the teaching of martial arts in informal settings, based on Sports Pedagogy and Opposition Games. Martial arts, historically linked to survival and combat, are now recognized as educational practices that promote physical, cognitive, and socio-emotional development. However, they still face prejudices related to violence. The study argues that, when well structured, they can promote discipline, respect, cooperation, and self-knowledge. In non-formal environments, such as gyms, clubs, and social projects, the teaching of martial arts must consider social, cultural, and pedagogical factors, adapting to the profile of practitioners, especially children. Often, the training of instructors is marked by the tradition of the "trade school," centered on empirical and hierarchical methods. In this context, Opposition Games emerge as a playful methodological alternative, capable of bringing students closer to combat modalities without the initial technical rigidity. Such games encourage controlled confrontations, respecting rules and promoting motor, cognitive, and social development, in addition to encouraging cooperation and conflict resolution. The research highlights the importance of reframing the rituals and traditions of martial arts, contextualizing them pedagogically so that they are understood and valued by students. For children, playfulness and subjectivity should be prioritized, avoiding an emphasis on performance and early competition. It can be concluded that teaching martial arts in non-formal contexts should be inclusive, critical, and humanized, integrating cultural and social values with modern methodologies that encourage participation, citizenship training, and well-being.